Growing importance of price: Investigating food values before and during high inflation in Germany - Corinna Hempel; Jutta Roosen (Agricultural Economics, 2024)
Abstract Considering the consumption-induced intensification of global challenges and the continuously changing consumer needs, it is important to understand the drivers of consumer food choices under external pressures. We applied best–worst scaling to elicit the relative importance of 11 food values and conducted latent class cluster analyses based on individual scores, allowing us to gain insights into distinctive consumer segments. Data were collected through online surveys of 1000 consumers in Bavaria, southern Germany, in November 2020 and November 2022. As expected, the relative importance of food value price has strongly increased during this period. Similarly, the price-sensitive segment has become larger in 2022 than in 2020, while the societal impact-centered segment has become much smaller in 2022. These findings call for target-specific measures to counteract this trend of increasing price focus that challenges sustainable dietary transitions.
Keywords: 330; best–worst scaling; food values; human values; latent class analysis; price inflation